Neutron detection with SiC detectors - Žiber, Ylenia (Matrika, 2022)
As the supply of 3He diminishes, a need for neutron detectors without the typical 3He-technology has arisen. Neutron detectors capable of detecting neutrons from fissile material are used to discover and inspect nuclear warheads and to prevent illicit trafficking of radiological materials. In recent years, semiconductor detectors have become most popular, especially those made from materials with a wide band gap like silicon carbide (SiC). The wide band gap at room temperature gives good spectral resolution in comparison to other semiconductor detectors (High Purity Germanium-HPGe) that require almost cryogenic temperatures. SiC semiconductor devices are widely used in power electronics, especially the easily fabricated 4H-SiC crystal. They have good spectral resolution at room temperature and have a high radiation tolerance. To detect neutrons, a layer of converter material is added to the detector. In the converter material charged particles are created from neutron reactions and detected in the SiC detector. Different materials can be used depending on the neutron energy spectrum of interest. For the detection of thermal neutrons, 10B and 6Li are typically used. Such detectors have been studied extensively, including an ongoing research and development effort with experimental testing at the Jožef Stefan Institute (JSI) TRIGA Mark II. research reactor.
Keywords: detekcija nevtronov; detektorji delcev; neutron detection; particle detectors; polprevodniški detektorji; semiconductor detectors